Proposal of a Soft Robotics Gripper Solution Fabricated by Additive Manufacturing - Pereira , P. J. P. D.; Campilho , R. D. S. G.; Kirgiz , M. S.; Kumar , M. V.; Raj , J. C. J. (Research and Developments in Engineering Research Vol. 6, 2023)
This work aims the creation of a soft robotics application, more specifically a soft gripper. The development of an original concept of a soft material handler (soft gripper) is intended, capable of performing the stipulated handling functions, through certain actuation mechanisms, meeting the requirements and constraints presented in the next sub-section. The final solution is based on an improvement procedure supported on structural Finite Element (FE) analyses. Cost analysis and prototype construction/validation finalize the evaluation. The gripper was designed, a prototype was executed, and tests were carried out to prove correct operation. These tests were successful showing the project as suitable for a real production environment.